The Comparative Analysis of Technological Content Knowledge (TCK) through The Digital Module and Google Classroom in Integrated Science Learning - Arfiani, Yuni; Fatkhurrohman, M. Aji; Hayati, Muriani Nur (Program Studi Pendidikan IPA, FKIP Universitas Pancasakti (UPS) Tegal, 2021)
The development of information technology has become one of the measures in ranking the nation's competitiveness. The success of technology integration in education comes primarily from curriculum content, learning processes, and the use of technology in education. A complex planning is needed in order to produce the output as expected, so in this case, the domain of capability in technological knowledge content (TCK) known as Technological Content Knowledge is needed, especially in science material. This study aims to analyze the comparison of learning outcome and TCK skills by user experience through used technology which is digital web modules and Google classroom. The subjects of this study were 6th semester students to obtain learning outcome. This study was a quasi-experimental study. This study used two e-learning platforms, namely digital modules and Google Classroom, to compare learning outcomes and questionnaire to analyse their TCK abilities. The study showed that there were differences using a digital module and using Google classroom by t- test. The use of digital modules further enhances cognitive learning outcomes than with Google classroom. The profile of TCK using the digital module is better than using GC.